Evaluation of pharmacy graduates’ competency during their Provisionally Registered Pharmacist (PRP) training / Mohammad Hafiz Othman - Othman, Mohammad Hafiz (2016)
Introduction: Competencies of graduates are the ultimate measure of the success and effectiveness of an educational programme. Despite the existence of competency and practice standards, the competency of pharmacy graduates in Malaysia has never been formally assessed. All pharmacy graduates are required to undergo 1+1 (PRP training and compulsory service, either with public or private sectors). This one year of service as a PRP, under the supervision of a preceptor, provides an excellent opportunity to assess the competency of pharmacy graduates. Objective: To assess the competency level of PRPs of pharmacy graduates from different universities in Malaysia. Competency areas that most PRPs lack and require enhancement in the curriculum will be identified. Method: A retrospective study on previous PRPs’ appraisal data (n=2439), obtained from the PBM database, consist of a summary of 9 areas of competencies from the period of 2013- October 2015. Results: PRPs who underwent training had a satisfactory level of competency based on the marks from the nine areas of competence [Record of Training and Experience of Provisionally Registered Pharmacist (PRP)] available in the PBM database. All nine competency areas showed a minimum achievement of 60% of PRPs who achieved high level marks (>80%) across the areas, except for Ward Pharmacy Practice competency which was only 43.09%. Low level marks (60-69%) in Ward Pharmacy Practice competence was also the highest. Thus, it is clear that PRPs mostly lack in Ward Pharmacy Practice competency. Conclusion: PRP performances varied across competencies; whereby, PRPs were thought to have a satisfactory level of competence during their training. However, this study does not include the PRP’s cGPA during their studies, along with unobserved characteristics which may include ability, social skills and determination that will probably reduce some of the limitations of this study.